2004
DOI: 10.1162/003465304323031058
|View full text |Cite
|
Sign up to set email alerts
|

Are Refugees Different from Economic Immigrants? Some Empirical Evidence on the Heterogeneity of Immigrant Groups in the United States

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
318
0
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 375 publications
(337 citation statements)
references
References 27 publications
10
318
0
9
Order By: Relevance
“…By tracking economic migrant and refugee cohorts across two censuses in the US-1980 and 1990-it is shown that refugees lag behind economic migrants during the first years after arrival, but that they eventually perform better than economic migrants [11]. More recent assessments of economic outcomes in the US [6] show that refugees earn less than other immigrant intake categories, but that this difference can be at least partially explained by differences in language ability, schooling, level of family support, mental health, and residential area.…”
Section: Existing Evidence For the Economic Integration Of Refugeesmentioning
confidence: 99%
See 1 more Smart Citation
“…By tracking economic migrant and refugee cohorts across two censuses in the US-1980 and 1990-it is shown that refugees lag behind economic migrants during the first years after arrival, but that they eventually perform better than economic migrants [11]. More recent assessments of economic outcomes in the US [6] show that refugees earn less than other immigrant intake categories, but that this difference can be at least partially explained by differences in language ability, schooling, level of family support, mental health, and residential area.…”
Section: Existing Evidence For the Economic Integration Of Refugeesmentioning
confidence: 99%
“…However, there are discrepancies in the results that purport this: some studies show that with increased time in the country, refugees perform as well as [6] or even better [11] than other non-economic immigrants; some show that the differences are small over time [5], while others argue that the gap remains substantial [12]. Explanations for these results vary from more general factors like language proficiency, level of education, and credential recognition, to more specific factors that highlight mental and physical health issues connected with asylum status, as well as to what extent the asylum-seeking procedure enhances (or hinders) the integration process.…”
Section: Resettled Refugees' Labor Market Integrationmentioning
confidence: 99%
“…Thus, Hatton and Williamson (1998) note that BTemporary emigrants would be less interested in making long-run investments in country-specific skills than would the emigrant who intended to stay^(even if many of those who Bintended to return to their families after a few years…failed to do so^); see also Cortes (2004). For example, Jews displaced as a result of Nazism and World War II rarely intended to resettle in their home countries, were typically under no illusions about the need to resettle elsewhere (e.g., the U.S. or Israel), and welcomed the opportunity to put down ties (marrying, raising families, etc.).…”
Section: Temporary Vs Permanent Relocationsmentioning
confidence: 99%
“…This is due, in part, to the difficulty of transferring a foreign credential; the story of the highly educated immigrant who was a professional back home, but now drives taxis or cleans buildings in the United States, is not an uncommon one (Mattoo et al, 2008). The effect of human capital also differs for particular nationalorigin groups, and presents a barrier especially for immigrants who lack documentation (Duleep and Regets, 1996;Kossoudji and Cobb-Clark, 1996;Cortes, 2004). While some research has highlighted the ''negative socialization'' of an American educational system for racial and ethnic minorities (Ogbu, 2008), American schooling also imparts key skills and norms that may aid immigrants in the economic incorporation process (Ainsworth-Darnell and Downey, 1998;Glick and White, 2003).…”
Section: Expanding Our Analytical Framementioning
confidence: 99%
“…For example, Cortes (2004) focuses on the effect of the ''implicit time horizon'' each group has, highlighting the fact that refugees lack the option to return to their country of origin and may in turn be more inclined than economic migrants to assimilate. However, sociological research emphasizes that the primary difference between these two groups is not necessarily these attitudinal perspectives, or other demographic and human capital factors, but rather their relationship to the states.…”
Section: Expanding Our Analytical Framementioning
confidence: 99%